2010
DOI: 10.1007/s10549-010-0824-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ixabepilone in ER/PR/HER2-negative (triple-negative) breast cancer

Abstract: Patients with ER/PR/HER2-negative (triple negative) breast cancer are not candidates for hormonal therapy or HER2-targeted agents. Ongoing research is aimed at identifying and understanding the benefit of established and emerging therapies in this disease setting. Triple-negative patients may achieve early responses to anthracyclines and taxanes, but novel strategies are also eagerly sought. The epothilone B analog ixabepilone acts to stabilize microtubules and demonstrates antitumor activity in recent breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 52 publications
1
49
0
3
Order By: Relevance
“…Fifty-three percent of triple-negative specimens were classified as bIII-tubulin-positive, compared with only 22% (21 of 97) of ER-positive patients and 28% (7 of 25) or HER2-positive patients. Ixabepilone has shown efficacy in TNBCs (55). However, long-term followup data are required to determine the prognostic value of bIII-tubulin overexpression; the current trial was not designed to collect long-term data.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-three percent of triple-negative specimens were classified as bIII-tubulin-positive, compared with only 22% (21 of 97) of ER-positive patients and 28% (7 of 25) or HER2-positive patients. Ixabepilone has shown efficacy in TNBCs (55). However, long-term followup data are required to determine the prognostic value of bIII-tubulin overexpression; the current trial was not designed to collect long-term data.…”
Section: Discussionmentioning
confidence: 99%
“…We reported a 10-y DFS rate of 76% in TNBC patients using cyclophosphamide dose intensification (10). Several ongoing studies involve new cytotoxic agents or targeted thera- pies (14). Inherent defects in DNA repair make TNBC a rational target for therapy based on polymerase (adenosine diphosphate-ribose) polymerase (PARP) (1); PARP inhibitors, with or without combination with platinum salts, are now at the forefront of clinical research in TNBC patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…Subset analyses of some trials have shown benefit with bevacizumab 107 , eribulin 75 , and ixabepilone 108 , but the asco guideline currently states that chemotherapy regimens should not be specifically tailored to various breast cancer subtypes (including tnbc) because of the absence of evidence proving differential efficacy. Interest in the role of poly adp-ribose polymerase inhibitors in the management of tnbc is increasing 109,110 , but standard treatments still include conventional chemotherapies such as anthracyclines and taxanes 6,111 .…”
Section: Triple-negative Breast Cancermentioning
confidence: 99%